Somatic Embryogenesis and Plantlet Regeneration from Immature Embryos of Papaya (Carica papaya L.) (Plant Tissue Culture and Biotechnology, 2023)
The experiment was carried out in the Laboratory of the Biotechnology Division, Bangladesh Agricultural Research Institute (BARI) to find out embryogenic responses and plantlets regeneration from immature embryos of papaya. The explants were inoculated on Murashige and Skoog (MS) medium supplemented with 0, 36, 45, 54 & 63 μΜ 2, 4-D and incubated in complete darkness at 25°C ± 1°C. Calli were obtained within 3 weeks of culture period. The highest percentage of explants (46.67) produced callus using 2, 4-D at a concentration of 45 μΜ. Calli were then transferred to somatic embryogenesis medium where embryogenic calli were developed, turned into greenish color and these somatic embryos were noticed within 10 days. The highest number of somatic embryos (86.33) was produced per explant on MS containing 54 μΜ 2, 4-D. Somatic embryos were regenerated on MS supplemented with different concentrations and combinations of BAP and NAA including GA3. The maximum regeneration percentage of somatic embryos (intact rooted plantlets) (54.17) was recorded in the medium supplemented with 0.4 μΜ each of BAP and NAA in combination with 10 μΜ GA3. The somatic embryo-derived plantlets were successfully established in small plastic pots with prepared soil and finally transplanted in the field. The plants were grown well and produced fruit under their natural environment.Plant Tissue Cult. & Biotech. 33(2): 97-106, 2023 (December)